Effect of physical culture minutes on the mental performance of students of secondary schools - Oleksiy Bulgakov; Alfiya Deyneko; Mikhailo Marchenkov (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to find out the impact on the mental performance of students of physical activity used in the process of physical education minutes and the lessons the overall cycle. Materials and Methods: a study was conducted in four secondary schools in Vinnitsa and Kharkov regions. The study involved 673 students grades 5-11. The study was conducted in two stages. In the first stage determines the change in the mental health of students during the school day. We used a technique A. Myunsberga. In the second phase of the study determined the impact of sports on the minutes and indicators of mental health of students. The study was conducted using a sample V. Anfimova proofreading. Results: the study shows the steady decline in indices of mental health of students during the school day. From the second to the sixth lesson mental performance of schoolchildren in the classroom overall cycle is reduced by 13.2%. Conclusions: the study also found that the performance of students in the classroom physical education minutes and the total cycle enhances their mental performance by 8%, compared with the lessons in which minute physical exercise have been conducted.